LLE for (Water + Ionic liquid) Binary Systems using [Cxmim][BF4] (x = 6, 8 and 10) Ionic Liquids - Maria Eugénia Macedo (2009)
Liquid-liquid equilibrium diagrams were determined for (IL + water) systems using the family of ILs 1-alkyl-3-methylimidazolium tetrafluoroborates, where the alkyl groups are hexyl and octyl ([Cxmim][BF4] with x = 6 and 8). The gravimetric method was used to determine the equilibrium compositions at temperatures ranging from 278.15 to 340.15 K. Both systems present an upper critical solution temperature (UCST), which increases from [C6mim][BF4] to [C8mim][BF4]. The experimental data were correlated using the NRTL and eNRTL models. The binary interaction parameters were calculated for each system and model, and good agreement between experimental and calculated equilibrium compositions was obtained. Finally, the apparent Gibbs energy, enthalpy and entropy of water solution in the ILs were calculated using a modified van't Hoff equation. The three thermodynamic functions were found to be positive for both ILs.